Financial deepening and integration of China and Singapore. - Goh, Melissa Huimin. (2008)
Our study compares the development of the financial markets of China and Singapore through the analysis of various financial deepening indicators. In our review, we will assess Singapore’s ability to leverage on to China’s growth, by examining the level of financial integration between Singapore and China.